Alternative tools as a guide for measuring the vertical dimensions of teeth on periapical radiographs - Deny Saputra; Yunita Savitri; Sri Wigati Mardi Mulyani; Aga Satria Nurrachman; Nastiti Faradilla Ramadhani; Syenia Ramandha; Marselina Sesaria Pratiknjo (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This research is aimed to find out the advantages of alternative tools as a guide for measuring the vertical dimensions of teeth on periapical radiographs and comparing the lengths of vertical dimensions of teeth on periapical radiographs with the actual lengths. Materials and Methods: This research is using analytical observational study with a cross-sectional study design. The research data were primary data from 30 periapical radiographs of two maxillary central incisors, which were photographed using a periapical projection with bisecting technique and a periapical film that had been attached with wire on the outer layer of the film wrap. The data were analyzed by a paired T-Test using SPSS software. Results: The p-value of ALT (Actual Length of the Tooth) for tooth 11 was 0.53 and for tooth 21 was 0.140. These results show a p-value > 0.05. Conclusion: There is no statistically significant difference between the calculation of tooth length on periapical radiographs using alternative tools and the calculation of actual tooth length so that alternative tools can be used as a guide for measuring the vertical dimensions of teeth on periapical radiographs.